Development of Arabic Teaching Materials Based on Multiliteracy and Augmented Reality - Khoirunnisa, Tsania; Nurhidayati, Nurhidayati; Ahsanuddin, Mohammad; Khasairi, Moh. (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2025)
The ineffective use of conventional student worksheets for learning fi’il madli among ninth-grade students at a Madrasah Tsanawiyah in Malang has resulted in limited comprehension and underutilization of technological tools, with 78.9% of 50 students experiencing learning difficulties and 90% scoring below the Minimum Completion Criteria. To address this problem, this study developed and evaluated SAMIL, a teaching material based on multiliteracy learning and Augmented Reality (AR), aimed at improving students’ understanding of fi’il madli. The research applied the Research and Development (R&D) approach using the ADDIE model, consisting of five stages: analyzing learning needs, designing teaching material concepts and instruments, developing the product, implementing product trials, and evaluating each stage. Quantitative data were gathered through needs analysis, expert validation scores, and responses from teachers and students, while qualitative data were obtained from classroom observations, interviews, and expert suggestions. The quantitative data were analyzed using descriptive statistics, and the qualitative data were interpreted using descriptive methods. The findings indicate that SAMIL achieved validation scores of 84.45% from subject matter experts, 91.47% from media experts, 90.28% from teachers, and 90.33% from 24 student users. These results demonstrate that the SAMIL materials are both feasible and practical for use in Arabic language instruction. Moreover, the integration of multiliteracy and AR in the teaching materials offers an engaging and interactive learning alternative that addresses students’ difficulties in mastering Arabic verb structures, thus contributing to more effective and technology-supported learning experiences in secondary-level Arabic education.